2021
DOI: 10.1007/s40273-021-01010-z
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for the Harmonisation and Improvement of Economic Evaluations of Personalised Medicine

Abstract: Objective The objective of this study was to develop guidance contributing to improved consistency and quality in economic evaluations of personalised medicine (PM), given current ambiguity about how to measure the value of PM as well as considerable variation in the methodology and reporting in economic evaluations of PM. Methods A targeted literature review of methodological papers was performed for an overview of modelling challenges in PM. Expert interviews were hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…For PM RCT, the small patient populations and more complex clinical pathways may increase uncertainty in CEA modelling results. Adding CEA of real‐world data as an adjunct to RCT data would improve confidence in a treatment’s effectiveness [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For PM RCT, the small patient populations and more complex clinical pathways may increase uncertainty in CEA modelling results. Adding CEA of real‐world data as an adjunct to RCT data would improve confidence in a treatment’s effectiveness [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cascade screening often add the health benefit of family members that are identified after an initial index patient tests positive to the health benefit of the index patient, resulting in a single QALY value "per index patient." 36 A single value combining the health gains of multiple patients is likely higher than the benefit "per patient who tested positive." Therefore, there may be some inconsistency in what is captured in the DQALY values that we extracted from the selected studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Interviewees expressed different opinions commenting on the innovative agreements recently signed between industries and payers to enable access to ATMPs. These innovative agreements include several different schemes designed to find a balance between the high cost of ATMPs and the uncertainty on their efficacy, including their long-lasting effectiveness; such schemes are generally referred to as Outcome Based Managed Entry Agreement, Risk Sharing Agreements, Value based price and Delay payment (20,(39)(40)(41). Managed entry agreements can facilitate patient access to treatments and are especially important for life-saving treatments where patients with high unmet needs should have early access.…”
Section: Pricing Of Atmpsmentioning
confidence: 99%